Análise comparativa entre métodos de ponderação de variáveis aplicadas ao índice de qualidade de efluente. - Cordeiro, João Mateus Barroso (2024)
The increase in the degradation and scarcity of water resources is a global issue. In this context, the assessment of effluent quality has increasingly attracted the interest of researchers, environmental managers, and policymakers. Thus, this study aimed to perform a comparative analysis of four variable weighting methods for the Effluent Quality Index (EQI). The first method is Entropy, the second is the Coefficient of Variation, applied in two configurations (Normal and Quartile). The other two methods include the Analytical Hierarchy Process (AHP) and its Gaussian variant (GAHP). Eight representative effluent variables were adopted. For organic matter, Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) were used. As a solids parameter, Total Suspended Solids (TSS) were utilized. As chemical indicators of nutrients, in addition to Phosphorus (P), the following were included: Ammoniacal Nitrogen (AMN), Total Kjeldahl Nitrogen (TKN) – encompassing Ammonia and Organic Nitrogen – Total Nitrogen (N), and finally, Thermotolerant Coliforms (TTC), as a biological descriptor. The application of the methods resulted in the assignment of weights, allowing for the ranking of variables. Consequently, it was possible to identify the most significant qualifiers in the composition of the EQI. The results also revealed the proximity between the methods, with TTC receiving the highest weights across all approaches, followed by COD, TSS, and BOD, which also demonstrated significant relevance. Nutrient-related variables, such as Nitrogen and Phosphorus, received lower weights, except in the GAHP method, which assigned greater weight to Phosphorus. In the analysis using five variables, the AHP method assigned the following weights: 0.223 for COD, 0.223 for TSS, 0.118 for NH3-N, 0.066 for P, and 0.370 for TTC. The Gaussian version of AHP showed a reordering of weights, with 0.251 for COD, 0.214 for TSS, 0.131 for NH3-N, 0.135 for P, and 0.269 for TTC. The Entropy, AHP, and Coefficient of Variation methods proved to be consistent and equivalent.